The End of Religious Studies (as we knew it). (17th June 2020) - Owen, Suzanne
Abstract : Fitzgerald's The Ideology of Religious Studies was published the year before I started my Master's degree at the University of Edinburgh and was brought to my attention by James Cox, my supervisor. It led me to question everything I had learned as a Religious Studies undergraduate and sparked my first essay (in 2001), titled "Religious Studies: What is it?" In it, I had seen the problem of "what is it?" as a methodological issue as well as a definitional one and predicted an expansion of Religious Studies along phenomenological lines. Today, while still recognising colleagues' fears that Fitzgerald's book undermines the study of religion, I rather see his critique as making the study of religion more important than ever, though not in the way I had described in my 2001 essay. My paper will revisit those early responses to the book (mine and others'), asking if we are indeed seeing the end of Religious Studies (as we knew it), and show how Fitzgerald's critique has instead opened up and transformed the study of religion, at least in my own research and teaching.